2020
DOI: 10.3390/joitmc6020034
|View full text |Cite
|
Sign up to set email alerts
|

Youth Awareness and Expectations about GMOs and Nuclear Power Technologies within the North American Free Trade Bloc: A Retrospective Cross-Country Comparative Analysis

Abstract: This study reports on the cross-country heterogeneity in youth awareness and expectations about genetically modified organisms (GMOs) and nuclear power technology (NPT) within the North American free trade area (NAFTA). Models are estimated with data on youth respondents from the USA, Canada and Mexico, using seemingly unrelated bivariate weighted ordered probit regression, with maximum simulated likelihood estimation. Our findings show that the diffusion of technology and information within the trade bloc, fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 96 publications
(119 reference statements)
5
14
0
Order By: Relevance
“…Relying on the evidence from studies using the theory of planned behavior in the United States, Craig and Sayers [58] reported young millennial risk perceptions and awareness of local clean energy initiatives, environmental orientation, and messaging to influence their attitudes toward federal clean energy policies. Similarly, in their recent cross-country investigation focusing on youths within NAFTA, Niankara & Adkins [59] reported a non-convergence in youths' awareness and expectations about NPT between the USA, Canada, and Mexico. However, their study found a 6.7% increased optimistic expectations from each level increase in NAFTA youths' NPT awareness.…”
Section: Previous Studies Of Npt Attitude and Acceptancementioning
confidence: 95%
See 4 more Smart Citations
“…Relying on the evidence from studies using the theory of planned behavior in the United States, Craig and Sayers [58] reported young millennial risk perceptions and awareness of local clean energy initiatives, environmental orientation, and messaging to influence their attitudes toward federal clean energy policies. Similarly, in their recent cross-country investigation focusing on youths within NAFTA, Niankara & Adkins [59] reported a non-convergence in youths' awareness and expectations about NPT between the USA, Canada, and Mexico. However, their study found a 6.7% increased optimistic expectations from each level increase in NAFTA youths' NPT awareness.…”
Section: Previous Studies Of Npt Attitude and Acceptancementioning
confidence: 95%
“…No prior study in the scientific discourse addressed public awareness and expectations about the technology in the country. Moreover, as pointed out in the North American context, youths play a vital role in the long-run development of nuclear energy programs [59]. It is therefore critical to get a clearer picture of contemporary UAE youths' awareness and expectations about the technology, so as to properly plan for the sustainable development of NPT in the country.…”
Section: Operation Of the Uae "Barakah" Nuclear Power Plantmentioning
confidence: 99%
See 3 more Smart Citations